On self-annihilation: bending the borrowed light - Sangalis, Dean, author; Thompson, Debby, advisor; Sloane, Sarah, committee member; McLeod, Alexus, committee member (Colorado State University. Libraries, 2016)
These stories attempt to capture greater meaning in narrative by employing a philosophical, though pragmatic, backbone: the idea of Harmonic Resonance, or a musical outlook of the world that acknowledges the pivotal role of light and sound. With our technological progress and the frightening amount of information now available, the world continues to become exceedingly complex, dissonant, and specialized. This specialization has arguably had the unfortunate side-effect of fragmenting society, including the individual, and I have tried here to share stories that instill our world instead with a sense of connection, mystery, and magic, while focusing on the difficulties inherent in the mundane. The struggle against personal self-annihilation, and the striving to bridge the ideal and the actual, is the main, recurrent thematic element that characterizes this work.